An Impact of Thickness on Structural, Optical, and Electrochromic Properties of wo3 Films Deposited by Sputtering for Smart Window Applications - Radhalayam, D (Springer, 2025)
DC magnetron sputtering (DCMS) was employed to deposit tungsten oxide (WO3) films on corning glass (CG) and fluorine-doped tin oxide (FTO) substrates. The influence of thickness variations on the film structure, surface morphology, optical properties, and electrochromic (EC) characteristics was explored using various analytical techniques including X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDX), ultraviolet–visible (Uv–Vis) spectroscopy, and cyclic voltammetry (CV). SEM analysis revealed that the thickness of the WO3- 4 film was around 500 nm. The films exhibited smooth surfaces with uniform distributions of small voids and grain clusters. XRD analysis confirmed the amorphous nature of the WO3 thin films. The optical properties of the WO3 films were evaluated using ultraviolet–visible-near-infrared spectroscopy. Films of varying thicknesses displayed different transmittance modulations between the bleached and colored states. The WO3- 2 films exhibited the highest transmittance modulation, reaching 81% at 600 nm. The lowest diffusion coefficient (8.97 × 10−9 cm2/C) was observed in WO3- 1, which also exhibited a coloring efficiency (CE) of 22 cm2. The CE values for WO3- 2, WO3- 3, and WO3- 4 were 38 cm2/C, 40 cm2/C, and 16 cm2/C, respectively. This study highlighted the significant impact of film thickness on color efficiency, which is a crucial factor in electrochromic (EC) applications. © The Author(s) under exclusive licence to Sociedade Brasileira de Física 2025.